2005
DOI: 10.1107/s1600536805022129
|View full text |Cite
|
Sign up to set email alerts
|

6-O-Acetylcodeine

Abstract: The title compound (systematic name: 6α‐acet­oxy‐4,5α‐ep­oxy‐3‐meth­oxy‐17‐meth­yl‐morphin‐7‐ene), C20H23NO4, crystallizes with one mol­ecule in the asymmetric unit. The mol­ecular structure exhibits features typical of morphine derivatives with a T configuration. The three‐dimensional packing is stabilized by inter­molecular C—H⋯N and C—H⋯π inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The molecule of (I) exhibits the T-shaped configuration characteristic of classical morphine opiates. The value of 86.62 (6)° for the dihedral angle between the mean planes of the A/B/C and D/E rings in (I) is comparable with that in codeine (88.94°; Canfield et al, 1987) and differs somewhat with that observed in 6-O-codeine [80.56 (8)°; Sonar et al, 2005;Kolev et al, 2005].…”
Section: S1 Commentmentioning
confidence: 47%
See 1 more Smart Citation
“…The molecule of (I) exhibits the T-shaped configuration characteristic of classical morphine opiates. The value of 86.62 (6)° for the dihedral angle between the mean planes of the A/B/C and D/E rings in (I) is comparable with that in codeine (88.94°; Canfield et al, 1987) and differs somewhat with that observed in 6-O-codeine [80.56 (8)°; Sonar et al, 2005;Kolev et al, 2005].…”
Section: S1 Commentmentioning
confidence: 47%
“…The absolute configuration of the chiral centres in the molecule is identical to those of the starting material, codeine. The main structural features of the molecule are very close to those of codeine (Canfield et al, 1987), heroin (Canfield et al, 1979), morphine (Gylbert, 1973) and acetylcodeine (Sonar et al, 2005;Kolev et al, 2005).…”
Section: Commentmentioning
confidence: 76%
“…Another structure determination of 6-O-acetylcodeine is reported in the following paper (Kolev et al, 2005).…”
Section: Commentmentioning
confidence: 99%
“…The new maxima in the IR-spectrum of (2) (Fig. 4(2)) in equal dichroic ratio leads to the observation of a 950 cm −1 band for γ =CH , indicating a stereo-structure typical for main part of codeine alkaloids [32][33][34][35][36][37][38]. Absorbance / Wavenumber (cm-1) …”
Section: Ir-ld Spectroscopy Of (1)mentioning
confidence: 99%
“…These data indicate a co-linearity of corresponding transition moments, which is realized in the frame of the stereo-structure of (1) shown in Scheme 2. X-ray data for similar compounds such as 6-O-acetylcodeine, codeine, heroin and morphine [32][33][34][35], show molecular structures characterized by a T-shape with a dihedral 3.2 IR-LD spectral analysis of (2) Comparison of the IR-spectra of codeine [20] and its H 2 PO − 4 salt (see Figs. 3(1) and 3(2)) indicated the following differences.…”
Section: Ir-ld Spectroscopy Of (1)mentioning
confidence: 99%